2017
DOI: 10.3847/1538-4357/aa7ca4
|View full text |Cite
|
Sign up to set email alerts
|

A Hot Downflowing Model Atmosphere for Umbral Flashes and the Physical Properties of Their Dark Fibrils

Abstract: Publisher rights © 2017. The American Astronomical Society. All rights reserved. This work is made available online in accordance with the publisher's policies. Please refer to any applicable terms of use of the publisher. General rightsCopyright for the publications made accessible via the Queen's University Belfast Research Portal is retained by the author(s) and / or other copyright owners and it is a condition of accessing these publications that users recognise and abide by the legal requirements associat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
56
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(67 citation statements)
references
References 74 publications
(78 reference statements)
8
56
3
Order By: Relevance
“…A polarimetric uniformity across quiescent and UF Stokes profiles suggests that the less energetic phase of UF morphology is being sampled; a consequence resulting from the upper-chromospheric formation height of the He I 10830 Å spectral line (Vernazza et al 1981;Avrett et al 1994). This is in contrast to upper-photospheric and lowerchromospheric observations of UF phenomena, which are obtained close to the formation heights of the UFs themselves (Grant et al 2018), hence producing a strong polarity change (de la Cruz Rodríguez et al 2013;Henriques et al 2017). When considered on a statistical basis (i.e., not isolating individual profiles that may inadvertently bias subsequent analyses), the excellent quality of the FIRS data and synthetic HAZEL spectra means that a complete study of vector magnetic field fluctuations can be undertaken.…”
Section: Hazel Inversion Codementioning
confidence: 99%
See 2 more Smart Citations
“…A polarimetric uniformity across quiescent and UF Stokes profiles suggests that the less energetic phase of UF morphology is being sampled; a consequence resulting from the upper-chromospheric formation height of the He I 10830 Å spectral line (Vernazza et al 1981;Avrett et al 1994). This is in contrast to upper-photospheric and lowerchromospheric observations of UF phenomena, which are obtained close to the formation heights of the UFs themselves (Grant et al 2018), hence producing a strong polarity change (de la Cruz Rodríguez et al 2013;Henriques et al 2017). When considered on a statistical basis (i.e., not isolating individual profiles that may inadvertently bias subsequent analyses), the excellent quality of the FIRS data and synthetic HAZEL spectra means that a complete study of vector magnetic field fluctuations can be undertaken.…”
Section: Hazel Inversion Codementioning
confidence: 99%
“…This increase in magnetic field deflections, through a combination of inclination and/or azimuthal changes, highlights the impact that developing shocks can have on their surrounding plasma. This is likely to be a consequence of the localized increase in adiabatic pressure resulting from the strongest UFs (Henriques et al 2017), which can subsequently deflect the surrounding magnetic field concentrations.…”
Section: Umbral Flash Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the NLTE radiative transfer code NICOLE (Socas-Navarro et al 2015) allows us to perform the inversion of observed Ca II 8542 Å (hereafter Ca 8542) Stokes profiles and the construction of semiempirical model atmospheres. Such inversions have been successfully performed for spectropolarimetric Ca 8542 observations and 3D magnetohydrodynamical simulations of solar features in the umbra and penumbra of sunspots (de la Cruz Rodríguez et al 2013;Henriques et al 2017), granular-size magnetic elements (magnetic bubbles) in an active region, and magnetic flux tubes (de la Cruz Rodríguez et al 2015a;Quintero Noda et al 2017). Recently, Kuridze et al (2017) performed NICOLE inversions of high-resolution spectroscopic data in the Ca 8542 line and found that the temperature in the middle and upper chromosphere close to the flare peak is enhanced up to ∼6.5-20 kK between logτ∼−3.5 and−5.5, decreasing gradually to pre-flare temperatures of ∼5-10 kK approximately 15 minutes after the peak.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most dynamic and widely recognized processes that creates multi-component chromospheric spectral lines is the propagation of magnetoacoustic waves, and their subsequent development into shock fronts, in the umbrae of sunspots [6][7][8][9][10][11]. Such umbral oscillations propagate energy upwards from the photosphere into the chromosphere, where the steep density drop results in the rapid increase of the velocity amplitude in an attempt to conserve energy flux, which is readily captured by the temperature-sensitive Ca II 8542 Å spectral line.…”
Section: Introductionmentioning
confidence: 99%